Identifikasi Penyakit Antraknosa Tanaman Jeruk Nipis [Citrus aurantifolia (Christm.) Swingle] di Desa Kertalangu Kecamatan Denpasar Timur - ARDINATA, I GEDE WIGUNA; SUDARMA, I MADE; SUNITI, NI WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.1, Januari 2017, 2017)
Identification of Leaf Spot Disease of Lime Plants [Citrus aurantifolia (Christm.) Swingle] in Kertalangu Village,District of East Denpasar.In Kertalangu Village, District East of Denpasar there are some plants lime getting anthracnose disease. Disease status is unknown and the plants are not too noticed by their owners. The purpose of this research was to identify the disease that attack lime plants. This research outlines the causes of disease, the extent of damage and the rate of infection of pathogens that attack lime plants. The research was conducted over three months since April until June 2015.This research has shown that the pathogen causing anthracnose disease in lime plants is Colletotrichum gloeosporioides. The disease incidence ranges from 26.46% - 35.87%, pathogen infection rate ranges from 0.0171 to 0.0157 per leaf per day (? 0.11), which means that 1000 leaves, infected 171-157 per day with the criteria of slow infection rates and the extent of damage or the disease severity ranges from 17.31% - 24.47% (> 10% - ? 25%), classified as mild criteria.
Keywords: Anthracnose, Colletotrichum gloeosporioides, disease incidence, infection rate and disease severity